Análise da expressão de proteínas envolvidas no manejo de cálcio cardíaco nos répteis píton (Python molurus), cascavel sul-americana (Crotalus durissus terrificus) e jacaré-de-papo-amarelo (Caiman latirostris) em jejum e nos períodos digestivo e pós-absortivo - Vasconcelos, Eliton da Silva (Universidade Federal de São Carlos, 2014)
The Sarcoplasmic reticulum calcium ATPase (SERCA), phospholamban (PLB) and the Na+-Ca2+ exchanger (NCX) proteins are essential for the cardiac calcium management and myocardial contractility in vertebrates. The increase in metabolic rate generated from mechanical and physiological process of digestion is known as specific dynamic action (SDA) and represents the energy cost of processing, digestion and absorption of food. In several groups of reptiles, feeding generates a rapid increase in rates of gas exchange, whose peak usually occurs one or two days after feeding, before suffering a slower decline and returning to preprandial values. Ingestion of large quantity of food demands a metabolic elevation and leads to indemnities related in ventricular mass and an increase in myocardial force contraction, avoiding an overload on the cardiovascular system. During the fasting, depletion of body mass occurs and it can also reach the heart muscle. To describe the importance and the changes in SERCA2, PLB and NCX proteins on the effects of feeding/digestion in reptiles broad-snouted caiman (Caiman latirostris), burmese phyton (Python molurus) and also by prolonged fasting in South-American rattlesnake (Crotalus durissus terrificus) Western blotting technique was used. We observed the homology existence between the proteins of reptiles in relation to mammals. The SDA increased expression of SERCA2 protein in three species of reptiles. The SDA can also have unduced the expression of an isoform and/or reduced phosphorylation at some active sites of SERCA2 in ventricular tissue of P. molurus. A direct relationship between the expression of SERCA2 with the PLB expression in C. durissus was observed. However in P. molurus and C. latirostris this relation does not exist. The three reptiles expressed the PLB with molecular mass of 50 kDa, whereas the mouse expressed 25 kDa. The vast evolutionary distance that separates mammals of reptiles may have caused the rise of isoforms between these groups, explaining this difference. The increased expression of NCX along with lower expression of SERCA2 and PLB in C. durissus in food group Fasting compared to the other two groups suggests a higher calcium mobilization in this feeding regime, which would be advantageous from the energy point of view. The expression of NCX with different molecular mass between the three species, a smaller number of consensus regions with the animals phylogenetically more distant and the great plasticity of NCX gene to form distinct proteins, suggest the expression of proteins isoforms with the reptiles studied in this research.
Keywords: Fisiologia comparada; SERCA2a; Fosfolambam; Trocador sódio-cálcio; Western blotting; Manejo cardíaco de cálcio; Phospholamban; NCX; Western blotting; Cardiac calcium management; Caiman latorostris; Crotalus durissus terrificus; Python molurus; CIENCIAS BIOLOGICAS::FISIOLOGIA